2016
DOI: 10.18363/rbo.v73n2.p.130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lesions caused by removable prosthetics

Abstract: The present study aimed to investigate the prevalence of injuries caused by removable prostheses in patients of clinical specialization in dentistry. Of 598 patients, 175 (29%) had some type of associated injury. The lesions found included erythematous candidiasis, inflammatory fibrous hyperplasia, inflammatory papillary hyperplasia, traumatic ulcer, angular cheilitis, irritative keratosis, and denture stomatitis. Inflammatory fibrous hyperplasia was the most prevalent lesion, found in 88 patients (50%), follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The most affected age group in this study were 51-60 years (29%) and 61 to 70 years (29%) while the least affected was 31-40 years Figure 2Table 2. Several authors claim that with an increase in age, there is a decrease in the salivary low which makes them prone to these lesions (Canger et al, 2009;Filgueiras et al, 2016). In this study, Denture Stomatitis was the most commonly seen lesion, which is 83% out of 100 patients and 33.3% out of 249 patients Figure 3.…”
Section: Resultsmentioning
confidence: 52%
“…The most affected age group in this study were 51-60 years (29%) and 61 to 70 years (29%) while the least affected was 31-40 years Figure 2Table 2. Several authors claim that with an increase in age, there is a decrease in the salivary low which makes them prone to these lesions (Canger et al, 2009;Filgueiras et al, 2016). In this study, Denture Stomatitis was the most commonly seen lesion, which is 83% out of 100 patients and 33.3% out of 249 patients Figure 3.…”
Section: Resultsmentioning
confidence: 52%
“…The etiology of IFH is strongly associated with chronic lowgrade trauma, which can generate local inflammatory processes, being observed a higher occurrence in dental prosthesis users. Interestingly, some cases of IFH caused by ill-fitting dental prostheses may present different morphological findings, such as the presence of chondroid or osseous metaplasia in the fibrous connective tissue (Cutright, 1972;Filgueiras et al, 2016;Tenorio et al, 2016). In the present cases, it was observed that all patients were ill-fitting removable dental prostheses users, being this the etiological factor associated with the rise of the lesions.…”
Section: Discussionmentioning
confidence: 47%
“…The treatment for IFH associated with CM is total excision of the lesion since there are no reports of recurrences or post-surgical complications. Besides that, it is necessary to make a new dental prosthesis to remove the traumatic factor that causes the rise of the lesion (Filgueiras et al, 2016;Tenorio et al, 2016). In this context, it is essential to recognize the clinical andhistopathological features of IFH associated with CM to perform an accurate diagnosis and avoid excessive and inappropriate treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A adaptação da prótese aos tecidos da cavidade oral, as relações oclusais, o tempo de confecção e uso da prótese, além da sua higienização, são alguns fatores que favorecem o surgimento de lesões relacionadas ao uso de prótese dentária 17 .…”
Section: Revisão Da Literaturaunclassified